The role of expectations in interest-rate determination - Cantoria, Filomena M. (1984)
The purpose of this paper is to understand the role of expectations in the determination of interest rates in the Philippines. The study focused on the interest rates of Philippine Treasury Bills from 1970 to 1980. The results show that the market forecast of the future levels of interest rates and that the market participants revise these expectations in a manner consistent with the error learning behavior. The changes in expectations as measured by the forward rates are a positive function of the forecasting errors. However, the forward rates are biased estimates of future rates, due to the presence of liquidity premium on longer-term maturities. This makes the Treasury Bills of varying maturities non-substitutable with each other. The factor that determine interest rates are the demand and supply of loanable funds, and inflation. The variables that measure these factors found with significant contribution in explaining the behavior of Treasury Bill Rates are; outstanding securities of the national government, outstanding securities of monetary authorities (Central Bank Certificate of Indebtedness), balance of payments, stock price index, U.S. discount rate, demand deposits and their turnover rates, and Consumer Price Index. The equations developed explain the levels of Treasury Bill rates, with high degree of significance, but display also positive serial correlation. As a consequence, the predictive power suffers from this limitation. However, the close relationship between the estimates for 1980 and 1981 using the regression coefficients of the equations and the forward rates implied by the term structure cannot be ignored.
Keywords: Interest rates; Rational expectations (Economic theory); Treasury bills -- Philippines -- 1970-1980